2013
DOI: 10.1089/tmj.2012.0188
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Telemetry Is Useful to Reduce Interdialytic Weight Gain in Patients with End-Stage Renal Failure on Hemodialysis

Abstract: Lacking compliance with liquid intake restrictions is one of the major problems in patients on hemodialysis and causes an increased mortality. In 120 patients on hemodialysis with an average interdialytic weight gain (IWG) exceeding 1.5 kg on at least 2 days during the 4 weeks preceding the intervention, the effect of telemetric body weight measurement (TBWM) on IWG, ultrafiltration rate, and blood pressure was evaluated over a period of 3 months. Patients of the telemetric group (TG) were supplied with automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 38 publications
0
37
0
5
Order By: Relevance
“…This study reviewed the 13 selected articles from various countries. Overall, 12 out of the 13 studies (92%) indicated that using technology-based interventions was effective at supporting health care in CKD patients (An, 2011;Blakeman et al, 2014;Cicolini et al, 2014;Cottrell, Chambers, & Connell, 2012;Cueto-Manzano et al, 2015;Gordon et al, 2016;McGillicuddy et al, 2013;Neumann et al, 2013;Ogna et al, 2014;Ong et al, 2016;Rifkin et al, 2013;Welch et al, 2013). This review contained several studies on chronic kidney disease: stage 3-4 chronic kidney disease (Cottrell et al, 2012), kidney transplant (Cueto-Manzano et al, 2015;McGillicuddy et al, 2013) and patients undergoing hemodialysis (Ogna et al, 2014;Welch et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study reviewed the 13 selected articles from various countries. Overall, 12 out of the 13 studies (92%) indicated that using technology-based interventions was effective at supporting health care in CKD patients (An, 2011;Blakeman et al, 2014;Cicolini et al, 2014;Cottrell, Chambers, & Connell, 2012;Cueto-Manzano et al, 2015;Gordon et al, 2016;McGillicuddy et al, 2013;Neumann et al, 2013;Ogna et al, 2014;Ong et al, 2016;Rifkin et al, 2013;Welch et al, 2013). This review contained several studies on chronic kidney disease: stage 3-4 chronic kidney disease (Cottrell et al, 2012), kidney transplant (Cueto-Manzano et al, 2015;McGillicuddy et al, 2013) and patients undergoing hemodialysis (Ogna et al, 2014;Welch et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The number of samples varied between 20-436 respondents. This systematic review included several study designs including RCTs (Blakeman et al, 2014;Gordon et al, 2016;McGillicuddy et al, 2013;Neumann et al, 2013;Ogna et al, 2014;Rifkin et al, 2013;Sevick et al, 2015), experimental queries (An, 2011;Cottrell et al, 2012) and pilot studies (Cueto-Manzano et al, 2015;Welch et al, 2013) which are intended to get a broad picture of the coverage of IT-based interventions. Some of the information technology-based interventions used in this study included smartphone/PDA, computers and internet/web (Cueto-Manzano et al, 2015;McGillicuddy et al, 2013;Ong et al, 2016;Sevick et al, 2015;Welch et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wednesday to Friday) as well as the average weekly IWG were significantly reduced as compared to controls. Required ultrafiltration rate and systolic blood pressure at the start of dialysis were reduced, while there was a tendency of a rise in diastolic blood pressure after 3 months of TBPM [44].…”
Section: Hemodialysis -Interdialytic Weight Gain and Arterial Hypertementioning
confidence: 91%
“…There has been research focused on monitoring and controlling medical conditions such as high blood pressure [8,9,10], diabetes [11,12], weight loss [13,14] and Chronic Obstructive Pulmonary Disease (COPD) [15,16,17]. Using new Information and Communication Technologies (ICT) in healthcare scenarios, such as wearable sensors, mobile devices and cloud computing, provides an opportunity for continuously monitoring health behaviors, which allows building a story around a person.…”
Section: Introductionmentioning
confidence: 99%